Kemampuan Ekonomi Regional Sulawesi Utara Menghadapi Arus Perdagangan Global - Mangowal, Benny (JBE (Journal of Business and Economics); Volume 8 No.2, 2009 JBE UNKLAB, 2009)
This article discusses globalization of Jeffrey Harrod who divides the globalization at least three types: firstly is globalization of communication: this is represented by the dramatic increase in the efficiency and speed of communication between individuals and organisations. Secondly is  globalization of media: The dominance of the multinational media corporations has pushed cultural products, an thirdly globalization of finance and production.  Globalization raise regional cooperation in economy with relatively high intensity. North Sulawesi has some advantages in term of strategic  greographic side in Asia Pacific region. In this context, North Sulawesi has a strong comparative advantages to Indonesia. So, export and tourism sectors should be facilitated by Sam Ratulangi Airport and Bitung Port. From the political aspect, the regional authonomy law has been carried otu, so this province can regulate and manage its local covernment. More importantly, this province must working harder to prepare human resources in facing globalization.